Preventive care offered by primary care and amputation of lower limbs in patient with diabetic foot - Isabel Cristina Ramos Vieira Santos; Ana Carla Florentino de Barros e Silva; Andréia Paula da Silva; Larisse Calou Pinheiro de Melo (Rev Rene)
The paper aims to verify the conduct preventive offered by basic care for the diabetic foot patient admitted in a large hospital in the city of Recife. Study of descriptive epidemiological approach, whose population corresponds to the patients admitted during the period August 2006 to August 2007, in the vascular clinic. There was a prevalence of 46% of patients aged over 65, male, with up to 4 years of schooling and income of up to 1 minimum wage. It found association between occurrence of amputations and the variables: knowledge of diagnosis, the way of knowledge of the disease, hold consultations each year after the diagnosis of DM, control of blood glucose, examination of the feet and guidelines for the care of feet. The results display the severity of diabetic foot complications, and show areas that need of major actions in the care provided by the Primary Care.